Quantifying Hail and Lightning Risk Factors Using Long‐Term Observations Around Australia. Issue 21 (27th October 2020) - Dowdy, Andrew J.; Soderholm, Joshua; Brook, Jordan; Brown, Andrew; McGowan, Hamish
Abstract: There is a growing need to better understand and quantify risks associated with extreme weather, including severe thunderstorm‐related hazards such as hail and lightning. Hail occurrence based on a long‐term archive of radar observations is presented for the first time in many temperate and subtropical regions of Australia, together with lightning observations from a ground‐based network of sensors. Mean monthly and hourly occurrence frequencies are examined for hail and lightning. Environmental conditions obtained from hourly reanalysis data indicate stronger wind shear on average for hail than lightning. The environmental conditions also indicate higher freezing levels on average for lightning than hail. These environmental differences provide plausible physical reasons for observed differences between hail and lightning climatology through the year. The study results are intended to help inform future planning and preparedness for thunderstorm‐related risks, including for severe weather forecasting and climate risk applications. Plain Language Summary: Natural hazards caused by thunderstorms, such as hail and lightning, can have severe impacts on society. Radar data are used to examine hail events at 10 Australian locations, and comparisons are made with lightning observations. Results are averaged over several years to calculate average annual values, including for the hourly and the monthly number of the hail and the lightning events. We find differences between hail and lightning events in the environmental conditions that they occur in. These environmental differences are found to help explain differences through the year in the average risk of occurrence of hail or lightning. The results are intended to enhance resilience in relation to thunderstorm‐related risks and provide guidance for extreme weather modeling and climate adaptation purposes. Key Points: Occurrence frequencies of hail and lightning are presented based on observations for a wide range of regions around Australia Environmental conditions are found to provide insight on spatiotemporal variations in hail and lightning activity Environments associated with individual hazard types are recommended for use in improved preparedness for thunderstorm‐related damages